Utilization of brown clay and cement for stabilization of clay - Mousavi S.; Leong Sing W. (Jordan University of Science and Technology, 2023)
Cements; Compaction; Consolidation; Highway engineering; Portland cement; Silica; Silica sand; Soils; Stabilization; Highway construction; Laboratory investigations; Maximum dry density; Optimum moisture content; Ordinary Portland cement; Stabilized clays; Unconfined compression; Vane shear; Soil cement